1999
DOI: 10.3354/meps184205
|View full text |Cite
|
Sign up to set email alerts
|

Benthic recovery following cessation of fish farming:a series of successes and catastrophes

Abstract: After the removal of fish cages at an intensive aquaculture site, the sedimentary environment was monitored over 23 mo for redox potential, total organic carbon and nitrogen, total phosphorus, algal pigments and macrofauna. Three sampling stations were established: one under the previous location of the cages (R-0), a second one (R-10) at 10 m distance from the edge of the cages and a control site (R-c) at > l km distance. At both stations near the farming site the sediment was initially found to be anoxic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
92
0
6

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(105 citation statements)
references
References 31 publications
7
92
0
6
Order By: Relevance
“…Eastern Mediterranean Sea: 199 stations from multiple sampling efforts conducted along the upper continental shelf of Crete (Karakassis & Eleftheriou 1997), in Heraklion Harbor (Lampadariou et al 2000), and in the Aegean and eastern Ionian Seas (Karakassis et al 1999. Samples are from sites with water depths of 10 to 190 m and salinity > 38 PSU.…”
Section: Methodsmentioning
confidence: 99%
“…Eastern Mediterranean Sea: 199 stations from multiple sampling efforts conducted along the upper continental shelf of Crete (Karakassis & Eleftheriou 1997), in Heraklion Harbor (Lampadariou et al 2000), and in the Aegean and eastern Ionian Seas (Karakassis et al 1999. Samples are from sites with water depths of 10 to 190 m and salinity > 38 PSU.…”
Section: Methodsmentioning
confidence: 99%
“…In Greece, (Karakassis et al, 1999), total benthic recovery had not been achieved after 23 months, while in British Columbia, Brooks et al (2003) reported complete biological remediation after 6 months. At a Scottish sea loch, Pereira et al (2004) found that sampled stations were highly to moderately disturbed after 15 months.…”
Section: Introductionmentioning
confidence: 99%
“…Such recovery seems to follow defined patterns (Pearson & Rosenberg, 1978;Diaz-Castañeda, Frontier & Arenas, 1993). Going against the classical paradigm of succession as a continuum, Sanz-Lázaro & Marin Page 14 Karakassis et al (1999) introduced a different perspective for the recovery process.…”
Section: Biological Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…This renders it possible for fish to attain fast individual body weight growth and good condition. Intensive fish farming carries the risk of water pollution from the decomposition of unconsumed feed as well as the products of fish metabolism (Lewkowicz and Lewkowicz 1976, Karakassis et al 1999, Pereira et al 2004.…”
Section: Introductionmentioning
confidence: 99%